2017
DOI: 10.2147/prbm.s129566
|View full text |Cite
|
Sign up to set email alerts
|

Testing domains of the healing experiences in all life stressors questionnaire in a cohort of HIV-infected and HIV-uninfected Chicago women

Abstract: PurposePatients may deal with issues of spiritual and religious meaning when coping with life-threatening or chronic illness. Researchers at the National Institutes of Health have developed the healing experiences in all life stressors (HEALS) questionnaire, an assessment to determine psychosocial spiritual adjustment to healing. Many measures assess religious and spiritual behavior, but there exists a need to capture the meaning of these factors in the process of healing. The instrument consists of spirituali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…Before receiving RCBT, these PLHIV experienced increased levels of shame, isolation, and decreased value and connections with God, others, the environment, and the self, and self-blame (Yu et al, 2018). This is consistent with the findings of the study of Mistretta et al (2017), which revealed that PLHIV with significant depressive symptoms also scored significantly lower in their spiritual wellbeing assessment. As Filipinos, the spiritual wellness of these PLHIV is culturally influenced to keep afloat due to resiliency and coping mechanisms in hurdling adversity (Magpusao, 2019), also with the help of PhilCHAN.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Before receiving RCBT, these PLHIV experienced increased levels of shame, isolation, and decreased value and connections with God, others, the environment, and the self, and self-blame (Yu et al, 2018). This is consistent with the findings of the study of Mistretta et al (2017), which revealed that PLHIV with significant depressive symptoms also scored significantly lower in their spiritual wellbeing assessment. As Filipinos, the spiritual wellness of these PLHIV is culturally influenced to keep afloat due to resiliency and coping mechanisms in hurdling adversity (Magpusao, 2019), also with the help of PhilCHAN.…”
Section: Resultssupporting
confidence: 92%
“…Spirituality is the lifelong relationship with the Divine, which leads to transformation of the individual (Feldmeier, 2016). PLHIV cope with their illness effectively due to their spiritual behaviors and meaning (Mistretta et al, 2017). There is an association between spirituality and health outcomes (Feldmeier, 2016;Ironson et al, 2016), despite various forms of changes and challenges in the form of increased levels of shame, self-blame, fear of disclosing HIV status, and isolation and decreased value and connections with God, others, the environment, and the self (Yu et al, 2018;Hortillas & Gayoles, 2018).…”
Section: Framework Of the Studymentioning
confidence: 99%
“…The measure also demonstrates adequate construct and discriminant validity (Radloff, 1977). Internal consistency in this study was strong at α = .90 and is consistent with previous research utilizing the CES-D with a sample of urban women living with HIV (Mistretta, Sloan, BrintzenhofeSzoc, Weber, & Berger, 2017).…”
Section: Methodssupporting
confidence: 89%